(untitled) (International Journal of Physiotherapy, 2020)
Background: Lateral Epicondylitis is the tendinosis of the extensor musculature of the forearm that has their common origin from the lateral epicondyle of the humerus due to angioblastic degeneration. The study aimed to determine and compare the effectiveness of MET and MaRhyThe in individuals with chronic lateral epicondylitis concerning pain, grip strength, and function. Methods: The study was a randomized clinical trial with 30 subjects divided into two equal groups, with 15 subjects in each group. Group A received MET for seven sessions, and Group B received MaRhyThe for one session. Both the groups received hot moist pack and conventional exercises for seven sessions. Visual Analogue Scale (VAS), Patient Rated Tennis Elbow Evaluation (PRTEE) Questionnaire, and Pain-Free Grip Strength (PFGS) were taken as the outcome measures. Results: Within-group paired sample t-test showed statistical significance in VAS at rest, VAS on activity, PRTEE, and PFGS with a p-value of 0.001 for all. However, between-group analysis using independent sample t-test showed statistical significance in VAS on activity and PRTEE with a p-value of 0.049 and 0.029, respectively, and clinical significance for VAS at rest and PFGS for Group B. Conclusion: The study concludes that both MET and MaRhyThe are effective in treating chronic LE concerning pain, improving function, and strength. However, MaRhyThe is more effective in pain reduction and improving functional activities.